Balancing maternal employment and child nutrition and health: a grounded theory study of rural communities in Northeastern Uganda - Joseph Lule Kyanjo; Alice Turinawe; Agneta Hörnell; Kristina Lindvall (BMC Public Health)
Abstract Background Child undernutrition remains a serious public health concern particularly in poor households where limited financial resources hinder proper child nutrition. Improving women’s access to productive resources and employment is crucial for addressing undernutrition. However, maternal employment may reduce the amount of time available for childcare, leading to poor child nutrition and health. This study explored rural community perceptions and experiences regarding maternal employment in relation to aspects of child nutrition and health in northeastern Uganda to inform the design of interventions that can effectively support maternal employment without compromising child nutrition and health. Methods Twelve gender-separated focus group discussions (FGDs) were conducted with pastoral and agro-pastoral communities in northeastern Uganda. Data from the FGDs were analysed using a constructivist grounded theory approach. Results Analysis of the FGD data revealed that cultural norms and economic pressure were crucial factors in maternal employment decisions. We constructed a model that represents maternal employment as a delicate balance to maximize the benefits for child nutrition and health while minimizing the negative consequences. The model comprises the core category, mothers’ solitary struggle for better child nutrition and health, and four interrelated categories: (1) mothers conforming to societal expectations, (2) mediating the effect of maternal employment on child nutrition and health, (3) suffering consequences of maternal employment, and (4) mothers striving for better child nutrition and health. Conclusion Access to income emerged as the main pathway through which maternal employment leads to better child nutrition and health. However, this benefit often comes at the cost of reduced time for childcare, which is perceived to be detrimental to child nutrition and health. Based on these results, enhancing access to productive resources and employment, particularly for women is crucial for addressing undernutrition. To ensure that maternal employment does not compromise childcare, policies must support the development and access to childcare options that are affordable and appropriate for women in rural areas and in informal employment to effectively balance employment and childcare.